Project-Based Learning Model Enhances Learning Outcomes in Computerized Accounting Subject (Case Study: SMK Negeri 1 Solok) - Refna Yetti (Journal of Hypermedia & Technology-Enhanced Learning, 2023)
The rapid advancement of technology in accounting systems requires educational institutions to adapt their teaching methods to meet industry demands. This study aims to evaluate the effectiveness of the Project-Based Learning (PjBL) model in enhancing student learning outcomes in the computerized accounting subject at SMK Negeri 1 Solok. The research is motivated by the pressing need for vocational education to bridge the gap between theoretical knowledge and its practical application, mainly using accounting software such as MYOB Accounting. Employing a classroom action research (CAR) approach, the study was conducted in two cycles, each comprising planning, action, observation, and reflection stages. The participants were 32 students from class XII AKL 4, who initially struggled to integrate accounting concepts with computerized applications. The findings demonstrate significant improvements in student performance, with average scores increasing from 71.85 in the pre-cycle to 85.61 by the second cycle, reflecting an improvement in mastery learning from 48.48% to 78.78%. The PjBL model fosters active participation, critical thinking, and collaboration, making learning more engaging and contextually relevant. This study contributes to the growing body of literature advocating for PjBL in vocational education by providing empirical evidence of its effectiveness in accounting education. Furthermore, the study highlights the importance of aligning educational strategies with technological trends to better prepare students for the workforce demands.